Tracking Memes in the Wild: Visual Rhetoric and Image Circulation in Environmental Communication - Jones, Madison; Beveridge, Aaron; Garrison, Julian R.; Greene, Abbey; MacDonald, Hannah (Frontiers in Communication, 2022)
Drawing on recent scholarship in environmental communication and rhetoric, this essay examines the role of visual circulation in digital environmental discourse. We argue that while environmental image circulation is often viewed as an ambivalent, or even performative, practice for environmental citizenship, it is also an important space for cultivating participatory culture online. Adapting a version of Laurie Gries’ “Iconographic Tracking” method, we offer five case studies that demonstrate how the digital circulation of environmental icons (or “econs”) and memes offers important tactics for engaging digital publics that can be deployed by public communication practitioners. Subsequently, we argue for a more nuanced view of image circulation as both a performative and a participatory strategy for environmental communication.